Effectiveness of Interactive Learning Strategies in Teaching World History - Mapacpac Jr., Greg W. (Technium Social Sciences Journal, 2023)
The study aimed to identify the effectiveness of interactive learning strategies in teaching world history of Grade 8 students. This quasi-experimental phase of the study involved 30 match-paired number of Grade 8 students of Southville I Integrated National High School, academic year 2019 – 2020. Statistical formula like mean, standard deviation, and paired t-test analysis were utilized in determining the significance of the differences between the formative, pre-test and post-test mean scores of the students in the experimental group and comparison group. Based on the findings of the study, it was concluded that there is no significant difference between the post-test mean score of the experimental and comparison group. Likewise, it was concluded that the two groups partly upheld the null hypothesis such that there is no significant difference between the mean scores of the students in the formative test. In the result, there is only one rejected hypothesis wherein the entire group had shown high scores because of the given learning strategies to the learners. The null hypothesis stating that there is no significant difference between the post-test mean score of the comparison and experimental group is hereby rejected. There is a large effect on the given exercises to the learners due to its own given problem that some of the students who had been experiencing the new way of teaching really give an evaluation of high scores rather than in the traditional way of teaching.